Flow Model Selection for Water Soluble Polymer Solutions - Mohammed, Muhanned A.R. (Nahrain University College of Engineering Journal, 2009)
This research deals with the effect of type and concentration of different polymer solutions on rheological behavior and apparent viscosity. All polymers studied in this work are water soluble, which are: XC-polymer, Carboxymethyl cellulose (two types), Hydroxyethyl cellulose and Polyvinyl alcohol. 55 experiments were performed with different polymer types and concentrations at 30 C ( 1 C). By using the Solver Add-in in Microsoft Excel®, the power law flow model was found to be the best fits the experimental results. The apparent viscosity of each polymer used at different concentrations was decreased with shear rates. It was found that XC-polymer solutions have higher shear stresses than other polymers. Also it was found that XC-polymer solutions have a higher viscosity, and its viscosity decreases much more than other polymer solutions used in this study.